Outside Back Cover: Volume 2 Issue 1. (26th March 2021) - Ni, Bing; Cölfen, Helmut
Abstract : Outside back cover image : Chirality is one of the most fascinating geometrical properties spanning from organics to inorganics. Organic chirality has been extensively explored in the past, and now inorganic chirality is emerging as a new "growth point". Organic and inorganic chiral compounds actually actively interact with each other in the material world, for example, in their synthesis, chiral resolution, catalysis, etc. The authors herein provide perspectives on the communications between inorganic and organic compounds, in the terms of chirality transfer and recognition. The transfer is mainly realized by material hybridization and asymmetric synthesis. The recognition is usually carried in the form of enantioselective adsorption of organics on inorganics, which might be followed by asymmetric catalysis. There are still many challenges in this field, and they mainly arise from the limited number of chiral inorganics with high quality. The authors provide some ideas about the fabrication of chiral inorganic materials from the perspective of nucleation theories, as well as some chiral resolution methods and applications. When the challenges have been alleviated, more opportunities in both fundamental researches and applications can be foreseen. (DOI: https://doi.org/10.1002/smm2.1021 )